1999
DOI: 10.1037/0021-9010.84.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy beliefs as a moderator of the impact of work-related stressors: A multilevel study.

Abstract: This study built on previous exploratory research (S. M. Jex & D. M. Gudanowski, 1992) that examined both self-efficacy and collective efficacy as moderators of stressor-strain relations. Based on survey data collected from 2,273 U.S. Army soldiers representing 36 companies, it was found that both self- and collective efficacy moderated the relationship between stressors and strains. Multilevel random coefficient model results revealed that respondents with strong self-efficacy reacted less negatively in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
434
3
27

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(495 citation statements)
references
References 56 publications
31
434
3
27
Order By: Relevance
“…Consistent with this, workrelated self-efficacy has been found to moderate the impact of workplace stressors on various indices of occupational strain, such that relationships are stronger, and thus more problematic, for employees with low levels of work-related self-efficacy, relative to employees with high levels of work-related self-efficacy (Jex & Bliese, 1999;Lu, Siu, & Cooper, 2005;Panatik, O'Driscoll, & Anderson, 2011;Schaubroeck, Lam, & Xie, 2000). In the present study, we extended this line of research by examining whether work-related selfefficacy could moderate the impact of a worksite stress management training (SMT) intervention on several occupational strain outcomes.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Consistent with this, workrelated self-efficacy has been found to moderate the impact of workplace stressors on various indices of occupational strain, such that relationships are stronger, and thus more problematic, for employees with low levels of work-related self-efficacy, relative to employees with high levels of work-related self-efficacy (Jex & Bliese, 1999;Lu, Siu, & Cooper, 2005;Panatik, O'Driscoll, & Anderson, 2011;Schaubroeck, Lam, & Xie, 2000). In the present study, we extended this line of research by examining whether work-related selfefficacy could moderate the impact of a worksite stress management training (SMT) intervention on several occupational strain outcomes.…”
Section: Introductionmentioning
confidence: 62%
“…Whilst several studies have found evidence to suggest that employees with low levels of work-related self-efficacy may be more vulnerable to workplace stressors (Jex & Bliese, 1999;Lu et al, 2005;Panatik et al, 2011;Schaubroeck et al, 2000), moderation effects were not found for all of the stressor-strain relationships examined. These inconsistent findings have led some researchers to examine the role other key variables whilst analysing the influence of work-related self-efficacy in the stressor-strain relationship.…”
Section: Work-related Self-efficacy and Intrinsic Work Motivationmentioning
confidence: 82%
See 1 more Smart Citation
“…Para a teoria social cognitiva, reações de estresse são vistas em termos de inefi cácia percebida de controle sobre as ameaças e exigências físicas e ambientais e que poderia estar associado a uma baixa vitalidade. Se as pessoas acreditam que podem lidar efi cazmente com os potenciais fatores de estresse não desenvolverão burnout, mas se elas acreditam que não podem controlar eventos aversivos, tendem a se angustiar levando ao burnout (Jex & Bliese, 1999). Outro caminho em que as crenças de autoefi cácia podem atuar é através dos processos afetivos, já que a crença na autoefi cácia infl uenciará a forma e a intensidade das reações afetivas, impactando sobre suas cognições e comportamento (Bandura, 1997).…”
Section: Discussionunclassified
“…The research of Jex et al shows that management self-efficacy has an important influence on the adjustment of individuals' work stress, that is, the lower the management self-efficacy, the greater the work stress [13]. Singh et al conducted a study of the managers from a refrigerator factory in India and found that managers with higher management self-efficacy have lower levels of job anxiety.…”
Section: Managerial Work Pressurementioning
confidence: 99%